From the Sultan to Atatürk Turkey - Mango, Andrew (Haus histories, 2009)
World War I sounded the death knell of empires. The forces of disintegration affected several empires simultaneously. To that extent they were impersonal. But prudent statesmen could delay the death of empires, rulers such as Emperor Franz Josef II of Austria-Hungary and the Ottoman Sultan Abdulhamid II. Adventurous rulers Kaiser Wilhelm of Germany and Enver Pasha in the Ottoman Empire hastened it. Enver's decision to enter the war on the side of Germany destroyed the Ottoman state. It may have been doomed in any case, but he was the agent of its doom. The last Sultan Mehmet VI Vahdettin thought he could salvage the Ottoman state in something like its old form. But Vahdettin and his ministers could not succeed because the victorious Allies had decided on the final partition of the Ottoman state. The chief proponent of partition was Lloyd George, heir to the Turcophobe tradition of British liberals, who fell under the spell of the Greek irredentist politician Venizelos. With these two in the lead, the Allies sought to impose partition on the Sultan's state. When the Sultan sent his emissaries to the Paris peace conference they could not win a reprieve.